Hockey legends - Italia, Bob, 1955- (Bloomington, Minn. : Abdo & Daughters, 1990)
Describes the lives of sports legends Wayne Gretsky, Bobby Orr, Gordy Howe, Bobby Hull, Phil Esposito
Keywords: Hockey players -- Biography